Essays in Industrial Organization - Esfahani, Hamideh <1978> (Alma Mater Studiorum - Università di Bologna, 2012)
This dissertation comprises four essays on the topic of industrial organization and environmental economics. The first essay investigates the profitability of horizontal mergers of firms with price adjustments. We take a differential game approach and both the open-loop as well as the closed-loop equlibria are considered. In the second essay, using the same approach as the first one, we study the profitability of horizontal merger of firms where the demand function is nonlinear. We take into consideration the open-loop equilibrium. The third essay studies the profitability of exogenous output constraint in a differential game model with price dynamics under the feedback strategies. The fourth essay investigates a second-best trade agreement between two countries when pollution spillovers are asymmetric to examine the strategic behavior of governments in using pollution taxes and tariffs under trade liberalization.